2020
DOI: 10.1093/hmg/ddaa232
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin dependence of social behaviour inCaenorhabditis elegansprovides a model to investigate an autism-associated gene

Abstract: Autism spectrum disorder (ASD) is characterised by a triad of behavioural impairments including social behaviour. Neuroligin, a trans-synaptic adhesion molecule, has emerged as a penetrant genetic determinant of behavioural traits that signature the neuroatypical behaviours of autism. However, the function of neuroligin in social circuitry and the impact of genetic variation to this gene is not fully understood. Indeed, in animal studies designed to model autism there remains controversy regarding the role of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 37 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…In all food leaving assays the number of food leaving events were counted manually during a 30 minute observation period using a binocular dissecting microscope (Nikon SMZ800; X10). A food leaving event was defined as when the whole of the worm's body came off the bacterial food lawn, as previously described [39]. Following each food leaving assay the % proportion of eggs, L1 and L2 progeny on the plate was calculated.…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…In all food leaving assays the number of food leaving events were counted manually during a 30 minute observation period using a binocular dissecting microscope (Nikon SMZ800; X10). A food leaving event was defined as when the whole of the worm's body came off the bacterial food lawn, as previously described [39]. Following each food leaving assay the % proportion of eggs, L1 and L2 progeny on the plate was calculated.…”
Section: Plos Onementioning
confidence: 99%
“…In accordance with previous findings we observed that N2 worms left the food lawn after 24 hours at a rate of approximately 0.088 leaving events/worm/minute (Fig 2). We had previously established a blunted food leaving response for the nlg-1(ok259) mutant [39] and this was used as an internal measure in the current assays (Fig 2).…”
Section: Screening Mutants Using Food Leaving Behaviour Identifies Asd Associated Genetic Determinants Of Social Behaviourmentioning
confidence: 99%
See 3 more Smart Citations